Discourse and digital practices : doing discourse analysis in the digital age - Jones, Rodney H.; Chik, Alice; Hafner, Christoph A. (London : Routledge, 2015)
'Discourse and Digital Practices shows how tools from discourse analysis can be used to help us understand new communication practices associated with digital media, from video gaming and social networking to apps and photo sharing. Fourteen eminent scholars including James Paul Gee and Camilla Vasquez address the challenges of working with digital texts and interactions, and illustrate how different approaches to discourse analysis can be adapted in the face of these new digital practices. This cutting-edge book will be of interest to advanced students studying courses on digital literacies or language and digital practices'--
Includes bibliographical references and index.
Keywords: Discourse analysis -- Data processing; Technological innovations; Digital; Social media